Hubungan Antara Pengetahuan dan Perilaku Pencegahan Gastritis Pada Penderita Gastritis di Ruang Lumba Bawah Blud RSUD Palabuhanratu - Hera Nurlaela; Mustopa Saepul Alamsah; Kartika Tarwati (Pusat Riset dan Inovasi Nasional, 2024)
Gastritis or often known as ulcers is inflammation of the stomach wall that is acute or chronic, gastritis can attack everyone and all ages. Factors that can influence gastritis are knowledge and behavior to prevent gastritis, knowledge is a very important element in shaping a person's actions, health behavior is a person's response to objects related to illness and disease. This study aims to determine the level of knowledge and behavior to prevent gastritis in gastritis sufferers in the lower lumbar room of the BLUD at Palabuhanratu Regional Hospital. This research is descriptive research with a cross sectional approach. The sampling technique in this research used accidental sampling, the number of samples taken was 80 respondents, namely patients suffering from gastritis in the lower lumbar room of the BLUD at Palabuhanratu Regional Hospital, data collection used a questionnaire and the results were presented in table form. Data processing and analysis used the SPSS version 26 program. The research results showed that there was a relationship between knowledge and gastritis prevention behavior in gastritis sufferers with a value of 0.000 where the value was smaller than 0.05 (alpha) so that H0 was rejected and Ha was accepted, meaning there was a relationship between knowledge. with efforts to prevent gastritis in gastritis sufferers in the lower lumbar room of BLUD Palabuhanratu Regional Hospital. It is recommended that health workers or nurses always provide education to patients about gastritis and how to prevent it so that patients understand and understand how important health is.